Current situation and key technology analysis of downhole blow-out preventer. (September 2020) - Wang, Guo; Wang, Zhihua; Niu, Xinming; Deng, Song; Liu, Yali; Fan, Hongkang; Hu, Yanfeng; Ma, Dongju
Abstract: It is difficult to meet the safety requirements of the existing well control technology with oil & gas exploration and development to deep complex formation. Therefore, it is important to carry out the analysis and research work of new blow out preventers. The downhole blowout preventer can provide a sealing well near the drill bit, which could eliminate the overflow in the bud. Thus, the downhole blowout preventer will be an additional protect barrier for the existing well control procedure. This paper introduces domestic and foreign downhole BOP situation, and analysis the structure and technical features of these downhole BOPs. The author discusses key technology of downhole BOP on the basis of analyzing the defect of the existing technology. It could be helpful for the research of downhole blowout preventer.